(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Sue Monk Kidd one of the most acclaimed writers from America and stands out from her contemporary fellow writers because of her works that reflects her real life. This paper is the perusal of Sue Monk Kidd’s historical novel The Invention of Wings. This novel talks about the friendship between two women characters Sarah Grimke and Hetty Handful. Sarah Grimke and Hetty Handful use their friendship as evidence that peace and equality between white people and black people is both possible and necessary. This paper is an attempt to investigate the problems faces by the women characters and how they overcome the problems by their friendship. Their unconventional relationship and their regard form one another create a substantial, life changing support for each woman. Sarah and Hetty come to comprehend and regard humankind in each other. The aim of this paper is to depict how the friendship and attachment of women characters Sarah and Hetty makes them to fly with their own wings.